2015
DOI: 10.1097/ico.0000000000000462
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative OCT-Assisted DMEK

Abstract: Live intraoperative OCT is useful to visualize and assess graft orientation in DMEK surgery. It enables faster graft positioning with less graft manipulation in the presence of severe corneal edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 11 publications
3
64
0
3
Order By: Relevance
“…Using the manual tracking feature described in Section 3.1, some of these systems also allowed the B-scans to be manually tracked to the tip of instruments during surgical maneuvers [118,121,122]. Alternatively, multiple (3-5) parallel B-scans spanning the site of interest could be acquired and displayed simultaneously to monitor motion orthogonal to the B-scan axis [123,132] (Fig. 6(b)).…”
Section: Live Two-dimensional Microscope-integrated Octmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the manual tracking feature described in Section 3.1, some of these systems also allowed the B-scans to be manually tracked to the tip of instruments during surgical maneuvers [118,121,122]. Alternatively, multiple (3-5) parallel B-scans spanning the site of interest could be acquired and displayed simultaneously to monitor motion orthogonal to the B-scan axis [123,132] (Fig. 6(b)).…”
Section: Live Two-dimensional Microscope-integrated Octmentioning
confidence: 99%
“…[118]. (B) Anterior eye surgery imaging protocol using five parallel and laterally offset B-scans spanning the area of interest [132]. The B-scan locations are overlaid on the surgical views.…”
Section: Live Two-dimensional Microscope-integrated Octmentioning
confidence: 99%
“…9,12,13,22,23,27,29,32,39,41,42 Using intraoperative OCT surgeons are able to obtain immediate feedback on the status of the surgical procedure.…”
Section: Anterior Segmentmentioning
confidence: 99%
“…27,29,41 Intraoperative OCT facilitates identification of graft orientation and appropriate unscrolling during graft manipulation. The DISCOVER study found that in~50% of cases the intraoperative OCT provided information that was discordant to surgeon impression.…”
Section: Anterior Segmentmentioning
confidence: 99%
See 1 more Smart Citation